Consistent traffic noise impacts few fitness-related traits in a field cricket - Gabrielle T. Welsh; Sophia C. Anner; Mary L. Westwood; Victoria Rockwell; Hannah O’Toole; Megan Holiday; Robin M. Tinghitella (BMC Ecology and Evolution, 2023)
Abstract Background Anthropogenic habitat change is occurring rapidly, and organisms can respond through within-generation responses that improve the match between their phenotype and the novel conditions they encounter. But, plastic responses can be adaptive or maladaptive and are most likely to be adaptive only when contemporary conditions reasonably mimic something experienced historically to which a response has already evolved. Noise pollution is a ubiquitous anthropogenic stressor that accompanies expanding urbanization. We tested whether the amplitude of traffic noise influences a suite of fitness-related traits (e.g. survival, life history, reproductive investment, immunity) and whether that depends on the life stage at which the noise is experienced (juvenile or adult). Our treatments mimic the conditions experienced by animals living in urban roadside environments with variable vehicle types, but continuous movement of traffic. We used the Pacific field cricket, an acoustically communicating insect that was previously shown to experience some negative behavioral and life history responses to very loud, variable traffic noise, as a model system. Results After exposing crickets to one of four traffic noise levels (silence, 50dBA, 60dBA, and 70dBA which are commonly experienced in their natural environment) during development, at adulthood, or both, we measured a comprehensive suite of fifteen fitness-related traits. We found that survival to adulthood was lower under some noise treatments than under silence, and that the number of live offspring hatched depended on the interaction between a female’s juvenile and adult exposure to traffic noise. Both of these suggest that our noise treatments were indeed a stressor. However, we found no evidence of negative or positive fitness effects of noise on the other thirteen measured traits. Conclusions Our results suggest that, in contrast to previous work with loud, variable traffic noise, when noise exposure is relatively constant, plasticity may be sufficient to buffer many negative fitness effects and/or animals may be able to habituate to these conditions, regardless of amplitude. Our work highlights the importance of understanding how the particular characteristics of noise experienced by animals influence their biological responses and provides insight into how commensal animals thrive in human-dominated habitats.